(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: There is still little information on health status in small communities and also according to the different cultural characteristics of people in different societies, the present study aimed to determine the rate of general health and its related socio-demographic factors in general population. Methods: A population-based cross-sectional study was conducted in Gonabad city, the North-East of Iran, in 2013. We used the 28-item General Health Questionnaire (GHQ-28) to examine general health status with the cutoff point of 23. The association between general health and socio-demographic factors were reported in crude and adjusted odds ratios with 95% confidence interval. Results: A total of 800 subjects were interviewed (Response rate=98%). The mean age was 35.5 (SD ± 10.6) years, 49.6% were female, 41.8% were aged 30 years or younger, and 65.9% did not have academic education. According to the GHQ-28, 24.7% of the participants were categorized as not healthy people. General health status was associated with age, sex, education level, family size, residency duration in neighborhood, and SES status. Conclusion: General health status varied according to both the individual and socio-economic factors. Socio-economic status seems to play an important role in enhancing individual’s health and then lead to improve the health of community. These findings also suggest that mental health programs should be targeted in women and elderly population by the newly established family physician plan.